Knowledge Integration and Competitiveness: a Longitudinal Study of an Industry Cluster - Connell, Julia; Voola, Ranjit (Emerald Publishing Group, 2013)
Purpose – This paper aims to examine how – and whether – members of an industry cluster share knowledge through networking as a means to improving competitive advantage and, in particular, whether trust is present in the knowledge-sharing process. Design/methodology/approach – The research involved three surveys utilizing a relationship marketing orientation (RMO) that were conducted at intervals (in 2004, 2008 and 2010) in addition to interviews with key cluster members, which were also conducted over a seven-year period. Findings – Knowledge sharing and integration were found to mediate the relationship between RMO and competitive advantage in 2004 and 2010 but not in 2008. Lower mean scores for trust were also found in 2008. Research limitations/ implications – The limitations are that the respondent numbers were small. It is recommended that one more survey is conducted in 2013 to determine whether the interventions reported here, the recruitment of new cluster staff and the continuing growth of the cluster, influence the comparative results over time. Practical implications – Knowledge sharing and collaboration within industry clusters requires active and discerning facilitation, particularly where new members are concerned. Originality/value – The paper adds value to the current research on industry clusters and knowledge sharing as surveys were conducted over a seven-year period that tracked changes as the cluster grew. The findings highlight the necessity of focusing on member relationships/collaboration during times of growth and change.